2014
DOI: 10.3390/v6062444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Watermelon Chlorotic Stunt Virus (WmCSV) from Palestine

Abstract: The incidence of watermelon chlorotic stunt disease and molecular characterization of the Palestinian isolate of Watermelon chlorotic stunt virus (WmCSV-[PAL]) are described in this study. Symptomatic leaf samples obtained from watermelon Citrullus lanatus (Thunb.), and cucumber (Cucumis sativus L.) plants were tested for WmCSV-[PAL] infection by polymerase chain reaction (PCR) and Rolling Circle Amplification (RCA). Disease incidence ranged between 25%–98% in watermelon fields in the studied area, 77% of leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…Since WmCSV is transmitted by whiteflies, this may explain the high incidence of disease in the surveyed fields. Disease incidence in some fields was observed to be more than 90%, which is similar to a previous study where disease incidence reached 98% in some watermelon fields surveyed in Palestine ( Ali-Shtayeh et al, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Since WmCSV is transmitted by whiteflies, this may explain the high incidence of disease in the surveyed fields. Disease incidence in some fields was observed to be more than 90%, which is similar to a previous study where disease incidence reached 98% in some watermelon fields surveyed in Palestine ( Ali-Shtayeh et al, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the majority of samples were infected with WmCSV, so we can confidently assume that WmCSV had a major role in symptom development and disease progression in these areas. There were significantly fewer samples with mixed infection compared to WmCSV infection in this study, whereas previous studies have reported that mixed infections with two or three whitefly-transmitted viruses are common in cucurbit fields in Lebanon, Palestine, and Jordan ( Abou-Jawdah et al, 2010 ; Al-Musa et al, 2011 ; Ali-Shtayeh et al, 2014 ). Hence, these viruses pose a great threat to cucurbit crops in Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The major advantage of RCA, in comparison to PCR and immunodetection, is its ability to detect circular DNA molecules without any a priori knowledge. When viruses are imported into a new country, such as tomato yellow leaf curl virus (TYLCV) in the Americas [ 189 ] or Northern Europe, [ 95 ] and squash leaf curl virus (SLCV) in the Middle East [ 103 ], they can be recognized. Samples with aSats, which were believed to be restricted to the Old World before, were found in Brazil, Venezuela, and Cuba [ 38 , 96 , 190 ].…”
Section: Get the Unknown And Unexpectedmentioning
confidence: 99%